B03 Making (anti-) Sense Out Of Huntingtin Levels In Huntington Disease. (17th September 2014) - Evers, M; Schut, M; Pepers, B; Atalar, M; Van Belzen, M; Faull, R; Roos, RAC; Van Roon-Mom, W
Abstract : Huntington disease (HD) is an autosomal dominant neurodegenerative disorder, characterised by motor, psychiatric and cognitive symptoms. HD is caused by a CAG repeat expansion in the first exon of the HTT gene, resulting in an expanded polyglutamine tract at the N-terminus of the huntingtin protein. Typical disease onset is around mid-life (adult-onset HD) whereas onset below 21 years is classified as juvenile HD. While much research has been done on the underlying HD disease mechanisms, little is known about regulation and expression levels of huntingtin RNA and protein. In this study we used a unique collection of human post-mortem HD brain tissue and fibroblast cells to investigate huntingtin mRNA and protein expression, as well as huntingtin antisense isoforms. In adult-onset HD brain samples, there was only a small but significant lower expression of mutant huntingtin mRNA compared to wild-type huntingtin mRNA, while protein expression levels were equal. Juvenile HD subjects did show a lower protein expression of mutant huntingtin compared to wild-type huntingtin protein. Additionally, in brain tissue we did not find any evidence for a reduced expression of huntingtin antisense, as we showed HTTAS_v1 expression in a homozygous HD patient. Finally, we have identified a novel huntingtin antisense isoform and named it HTTAS_v2.2. Our study shows an intricate mechanism of huntingtin RNA and protein regulation of expression with slightly less mutant huntingtin mRNA, but equal wild-type and mutant huntingtin protein levels in adult-onset HD, indicating subtle differences in huntingtin protein expression between adult-onset and juvenile HD.